GE_GERICHTE P/19570/2024 vom 16. Dezember 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;SECRET DE FONCTION;ERREUR DE DROIT(DROIT PÉNAL);PRINCIPE DE PUBLICITÉ | CPP.310; CP.320; CP.21; CPP.69